SECONDARY METABOLITE CHARACTERISTICS OF HETEROTROFIC BACTERIA PRODUCTION AS ANTIMICROBIAL AT DIFFERENT SALINITY - Apriyola, Nadya; Feliatra, Feliatra; Nurulita, Yuana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2020)
This research was conducted from March-June 2019. The purpose of this study was to determine the characteristics of secondary metabolites prduced by of heterotrophic bacterial from sea water Sungai Kayu Ara Village, Siak Regency as an antimicrobial and to determine the storage time of these bacteria by measuring at the optimal growth time. Five bacterial secondary metabolite extracts used were B, C, D, and H (B. cereus) and J (V. fluvialis) obtained from the collection of Marine Microbiology Laboratory, Department of Marine Sciences, Faculty of Fisheries and Marine sciences, University of Riau. phytochemical test showed that extracts of isolates B, D, and H contained saponin compounds, while isolate J contained flavonoid compounds, however, all extracts contained alkaloid compounds. Antimicrobial test indicated that J extract inhibited A. Hydrophila at concentration 500 µg/ml but the extract could not inhibit V. algynolyticus and Pseudomonas sp concentrations determined. In the bacterial storage time test, the optimal growth of each bacterial concentration at was 7th day incubation and decreased on the 14th day.